Anthropological literature in Chile - Pilar Valenzuela Rettig (Revista Chilena de Literatura, 2017)
Anthropological literature in Chile is an intercultural and interdisciplinary literature, written by contemporary Chilean anthropologists and archaeologists. They are looking for a new way of communicating their field work and anthropological knowledge. This article presents the main conclusions of a research whose objetive was to define and characterize anthropological literature as an intercultural literature.